Marianne Moore : The Poet's Advance - Stapleton, Laurence (Book collections on Project MUSE., 1978)
This book provides a full-scale interpretation of Marianne Moore's poetry and prose, starting with her early experiments and exploring the range and variety of her artistic achievement. It portrays the self-discipline and the fidelity to experience that were the source of her originality. Laurence Stapleton's study of unpublished manuscripts, including notebooks, drafts of poems, and correspondence, supports her account of Marianne Moore's progress in the mastery of form. Her methods of work in the early satires, in the more openly constructed poems of the 1930s, and in the major ones of World War II, emerge in the context of her life as a professional writer. The spontaneity and inventiveness of her later books resulted from her La Fontaine translation and her response to music, to painting, and to the changing American scene.Constantly in view are Marianne Moore's literary relationships with Ezra Pound, T. S. Eliot, Wallace Stevens, and William Carlos Williams, as well as her appeal to a large circle of readers that made her become "New York's laureate." The insight that may be gained from this book should bring a better understanding of her accomplishment and of her place in American literature.Originally published in 1978.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.